Price Controls and Electoral Cycles - Asilis, Carlos (IMF Working Papers; Working Paper, 1993)
This paper studies the interactions between electoral considerations and the imposition of price controls by opportunistic policymakers. The analysis shows that a policy cycle emerges in which price controls are imposed in periods leading to the election, and removed immediately afterwards. The shape of the cycle is shown to depend on the periodicity of elections, the relative weight attached by the public to inflation as opposed to the macroeconomic distortions associated with price controls, the nature of wage contracts, and the degree of uncertainty about the term in office.